2020
DOI: 10.1177/0734242x20958065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elevated temperature on solid waste shear strength and landfill slope stability

Abstract: Slope instability occurs in landfills owing to increased internal temperatures. However, strength characteristic tests for solid waste (SW) and landfill slope stability (SS) calculations that consider temperature variations are scarce in the literature. In this study, we conducted triaxial tests on SW under a range of temperature conditions and proposed the circular slide method (CSM) for calculating SS in consideration of temperature effects. SW cohesion decreased linearly with increasing temperature, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Larger amounts of kitchen waste are received by landfills in Asia than by landfills in Europe and North America, meaning that leachate is generated more quickly in landfills in Asia than in Europe and North America (Gao et al, 2015). The LL is, therefore, generally high in MSW landfills in Chinese and other Asian cities (Jayaweera et al, 2019;Merry et al, 2005;Shi et al, 2020;Somani et al, 2020;Zhan et al, 2008). In this study, the LL was set to 10 m from the landfill top and 40 m from the landfill bottom.…”
Section: Model Calculationmentioning
confidence: 99%
“…Larger amounts of kitchen waste are received by landfills in Asia than by landfills in Europe and North America, meaning that leachate is generated more quickly in landfills in Asia than in Europe and North America (Gao et al, 2015). The LL is, therefore, generally high in MSW landfills in Chinese and other Asian cities (Jayaweera et al, 2019;Merry et al, 2005;Shi et al, 2020;Somani et al, 2020;Zhan et al, 2008). In this study, the LL was set to 10 m from the landfill top and 40 m from the landfill bottom.…”
Section: Model Calculationmentioning
confidence: 99%
“…According to the temperature-controlled triaxial test results of the degradation-limited synthetic waste, the composition of which is referred to the on-site waste (the dry density 0.66 g cm -3 , the specific gravity 1.982, and the void ratio 2.0; containing 24% kitchen waste, 12% paper, 5% bamboo, 4% fibre and 12% plastics), Shi et al (2020) provided linear relationships between strength parameters and temperature at different axial strains. This article adopted these hypotheses and set ε a = 15% as the failure strain (Towhata et al, 2004), in which case the cohesion of MSW decreases with an increase in temperature by 0.483 kPa/°C.…”
Section: Effects Of Temperature On the Shear Strength Of Msw And The ...mentioning
confidence: 99%
“…Compared with the passive wedge, the active wedge is easier to slide along the back slope because β > θ; thus, the friction angle of back slope slip surface is more critical to wedge stability than that of bottom slope slip surface; as a result, the ratio of back slope inclination to the frictional coefficient, tanβ/tanδ 20 , can be chosen to represent the mechanical property of the slip surface. In the case of the active wedge sliding through the waste fill, the study of Shi et al (2020) has revealed that ϕ sw changes little with temperature; thus, δ 20 = ϕ sw . The change of tanβ/tanδ 20 reflects the effect of different liner materials or the waste composition change due to degradation on the mechanical property of slip surface.…”
Section: Parametric Studymentioning
confidence: 99%
See 2 more Smart Citations